ICP: Volmume 12, n° 2, 2011 - Full Issue - journal system (Identity, Culture and Politics, 2011)
Table/Contents Le mot des rédacteurs en chef / Notes from the editors ............................. v How China’s “Trade Not Aid” Strategy Became Construed As Charitable Help : Deconstructing the “Touching” Idyll of Li Li’s Investment in Africa Philip Hsiaopong Liu ............................................. 1 Les économies africaines doivent elles avoir peur de la Chine ? Herman Touo .......................................................... 19 Soundings in Kindred Struggles : The Egyptian Voice in Gandhi Anil Nauriya .............................................. 43 L’Afrique entre Dieu et dieux : le mouvement pendulaire de la foi. Assouman Bamba ................................................. 67 Socio-Cultural Stratification of India Iqtidar Karamat Cheema ....................................... 83 The ’Universal’ in science as a Dilemma for scholarship in Africa Olajide Oloyede .................................. 95 Book Review Françoise Raison-Jourde et Gérard Roy, Paysans, intellectuels et populisme à Madagascar. De Monja Jaona à Ratsimandrava (1960-1975), Paris, Karthala, coll. Hommes et sociétés, 2010, 490 p. Par Solofo Randrianja ............................................ 109